Symbolism and Cultural Meaning in the Sedekah Bumi Tradition of Sukadiri Village, Banten: An Ethnographic Study - Gufron, Iffan Ahmad; Aspandi, Aspandi; Aspita Septiani, Lutfiyah (AL-TAHRIR, 2025)
This research examines what the Sedekah Bumi tradition in Sukadiri Village, Banten, symbolizes, and the significance of the Sedekah Bumi tradition in Sukadiri Village, Banten, and understanding the need for emphasis in modern-day Islamic society. The objectives are: (1) to decipher the description of the symbols of the Sedekah Bumi ritual, (2) to interpret the meaning contained in the symbols Sedekah Bumi. With the assumption of the phenomenon in qualitative ethnographic approach, the author studies the offering tradition in Sedekah Bumi and the ritual itself, the author substantive the people and culture by the which the Sukadiri people interpret the offering intrapersonal and the offering meditation and ritual dialogue by the interdisciplinary means of Sukadiri people and culture, the author studies the primitive documentation and her narrative, the dialog and cultural documentation. The author transcribes cultural documentation, draws conclusions, presents information, and records reinformation. The author provides documentation, her narrative, the dialogue, and cultural documentation. Analysis aims to order ideas and her narration to serve as the primary information.